Effect of intensive karate kyokushinkay exercise on body water content - Załuska, Alicja; Czapska, Mirella (Journal of Education, Health and Sport, 2018)
An intensive combat sports practice affects body water content. Changes in total body water (TBW), extracellular body water (ECW) and intracellular body water (ICW) affect power output and forearm maximum strength. Unfortunately, the effect of intensive karate kyokushinkay training with full contact fighting on body composition has not been documented. The purpose of the study was to analyze the effect of intensive karate kyokushinkay training with full contact fighting on body water distribution in healthy volunteers.